Desain Game Edukasi Berbasis Android dan PC Menggunakan Software RPG Maker MV guna Mendukung Konsep P5 - Maharani, Rachma; Nazarmi, Novi Aprilia; Sabrina, Hidayatul Sani; Wijayanti, Chandra (Lembaga Yasin AlSys, 2023)
Currently the government through the Ministry of Education and Culture is holding and promoting Character Education for Indonesian students to form a Pancasila Student Profile in order to reduce and overcome problems related to student character in the 21st century. Through the Pancasila Student Profile which includes 6 dimensions, namely faith and piety to God Almighty and having noble character, global diversity, critical thinking, mutual cooperation, creative and independent Indonesian education wants to make students in all corners of the country to better understand, appreciate and implement the values of Pancasila. It is not easy to make an appropriate learning plan in instilling character education that is integrated into subjects, educators must align their competencies in the current digital transformation era through independent training activities, surfing in cyberspace to add insight and collaborate with colleagues, Head Schools, and School Superintendents on what media should be given to students. So that from this subject emerged an innovation to support teaching and learning activities and attract students' motivation to learn by utilizing one of the learning media, namely educational games. This innovation is reinforced by survey results which state that the average game player is between 7-30 years old with an 80% percentage aged 7-21 years being a group of children to teenagers who are very fond of playing online games. So a research concept was designed using a quantitative descriptive approach that uses numerical data and is treated statistically or quantitatively since the data was collected.